Brain MRI Phenotypes Associated with Polymorphisms at or near the MAPT (Microtubule Associated Protein Tau) and COASY (Coenzyme A Synthase) Genes. (29th May 2020) - Chambers, Emily; Hermann, Evan; Davis, Danielle; Montgomery, Mckale; Lucas, Edralin; Chowanadisai, Winyoo
Abstract: Objectives: Impaired metal homeostasis in the brain has been reported in neurodegenerative diseases such as Alzheimer's Disease and Parkinson's Disease and can be detected using magnetic resonance imaging (MRI). Many factors, including genetics, affect brain metal accumulation and the risk of neurodegeneration or premature brain aging. Our objective is to uncover independent association signals at chromosome 17 associated with susceptibility-weighted MRI (swMRI) intensities in the caudate and putamen. Methods: Conditional and joint association analysis by GCTA-COJO was performed on the summary statistics dataset from a genome-wide association study (GWAS) on brain swMRI phenotypes from 7778 healthy adults of European descent aged 40–69 years from the UK BioBank. Independent association signals (single nucleotide polymorphisms or SNPs) found by GCTA-COJO were grouped further by SNPclip to identify additional candidate SNPs in high linkage disequilibrium (LD) (R2 > 0.8, P  < 5.0 × 10–8) with the independent lead/index SNP at each signal. Correlations were performed to show the similarity of impacts (beta) of SNPs significantly associated with MRI differences in both caudate and putamen at one locus. Results: There are 2 independent and distinct loci at chromosome 17 associated with MRI differences in the putamen, whereas there is only 1 locus for the caudate. One locus for the putamen is associated with the MAPT H2 haplotype, which has been linked to different neurological diseases. Another locus for both putamen and caudate is located near the genes COASY, NAGLU, and MLX, which are all plausible candidate genes for brain metal accumulation. For one locus identified by GCTA-COJO, there are 19 SNPs in LD (R2 > 0.8) and overlapping in both the caudate and the putamen. The effects (beta) of the SNPs in the putamen and caudate are highly correlated across both brain regions (R2 = 0.907, P -value = 0.000921). Conclusions: There is likely 1 signal from the COASY/NAGLU locus on chromosome 17 affecting both brain regions. The signal from the MAPT locus only affects the MRI pattern seen in the putamen. These results connect genetics with brain MRI patterns and an individual's risk for neurodegenerative diseases. Funding Sources: This work was funded by grants from the Oklahoma Center for the Advancement of Science & Technology and the Oklahoma Agricultural Experiment Station.